Contrast-Induced Acute Kidney Injury: Review and Practical Update. Issue 13 (October 2019) - Morcos, Ramez; Kucharik, Michael; Bansal, Pirya; Al Taii, Haider; Manam, Rupesh; Casale, Joel; Khalili, Houman; Maini, Brijeshwar
Contrast-induced acute kidney injury (CI-AKI) is an important consideration in patients undergoing cardiac catheterization. There has been a continuous strive to decrease morbidity and improve procedural safety. This review will address the pathophysiology, predictors, and clinical management of CI-AKI with a concise overview of the pathophysiology and a suggested association with left atrial appendage closure. Minimizing contrast administration and intravenous fluid hydration are the cornerstones of an effective preventive strategy. A few adjunctive pharmacotherapies hold promise, but there are no consensus recommendations on prophylactic therapies.